Proinflammatory Signals as Fuel for the Fire of Hematopoietic Stem Cell Emergence. Issue 1 (January 2018) - Espin-Palazon, Raquel; Weijts, Bart; Mulero, Victor; Traver, David
Abstract : Hematopoietic stem cells (HSCs) have the extraordinary ability to both self-renew and generate all mature blood cell lineages. The ability to produce or expand patient-derived HSCs in vitro would greatly improve the outcome for patients with blood disorders that are currently treated with allogeneic HSC transplantation. Many laboratories have been working to identify the signals required for HSC emergence in their native environments to apply this knowledge in vitro . Recently, several signals traditionally known to underlie classical inflammation have emerged as essential regulators of HSC development. In this review we synthesize the findings that have established inflammatory cues as key regulators of HSC development. Trends: HSC specification occurs during early stages of embryonic development. A complex network of signals orchestrates this process. Attempts to replicate these signals in vitro to instruct embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) to produce bona fid e HSCs have been unsuccessful to date. Adult HSCs are armed with immune receptors (TLRs and NLRs) to sense infection and stress signals. They respond with changes in gene expression, producing large amounts of proinflammatory cytokines that contribute to myeloid differentiation and emergency hematopoiesis to fight the cause of infection. Proinflammatory signals and immune cells are required to specify HSCs in the aseptic embryo. Translational use of these in vivo immunomodulators to in vitro protocols may improve efforts to generate functional HSCs.